Improvement of resistance to rice blast and bacterial leaf streak by CRISPR/Cas9-mediated mutagenesis of Pi21 and OsSULTR3;6 in rice (Oryza sativa L.) - Yang, Jinlian; Fang, Yaoyu; Wu, Hu; Zhao, Neng; Guo, Xinying; Mackon, Enerand; Peng, Haowen; Huang, Sheng; He, Yongqiang; Qin, Baoxiang; Liu, Yaoguang; Liu, Fang; et al. (Frontiers in Plant Science, 2023)
Rice (Oryza sativa L.) is a staple food in many countries around the world, particularly in China. The production of rice is seriously affected by the bacterial leaf streak and rice blast, which can reduce rice yield or even cause it to fail to be harvested. In this study, susceptible material 58B was edited by CRISPR/Cas9, targeting a target of the Pi21 gene and a target of the effector-binding element (EBE) of the OsSULTR3;6 gene, and the mutants 58b were obtained by Agrobacterium-mediated method. The editing efficiency of the two targets in the T0 generation was higher than 90.09%, and the homozygous mutants were successfully selected in the T0 generation, and the homozygous mutation rate of each target was higher than 26.67%. The expression of the edited pi21 and EBE of Ossultr3;6 was significantly reduced, and the expression of defense responsive genes were significantly up-regulated after infected with rice blast. The lesion areas of rice blast and bacterial leaf streak were significantly reduced in 58b, and both resistance was effectively improved. Furthermore, the gene editing events did not affect the agronomic traits of rice. In this study, the resistance of 58b to rice blast and bacterial leaf streak was improved simultaneously. This study provides a reference for using CRISPR/Cas9 to accelerate the improvement of rice varieties and the development of new materials for rice breeding.